PROSPECTS FOR DEVELOP THE PRODUCTION OF BIOFUELS IN THE EUROPEAN UNION AND ROMANIA - Marcela, Stefan (Economics of Agriculture, 2012)
The development of biofuels contribute to increasing energy security of states and improve balance of payments by reducing oil imports. . Extending benefits of biofuels production should be evaluated carefully since their costs are not small and can irreversibly affect the welfare of rural communities and regions, especially with reference to environmental costs (reduction of areas covered by forests, adverse effects on soil, water reserves, biodiversity etc.).. The production of biofuels in our country is at the beginning, but Romania has great potential for growing energy crops and biofuels.